Khru Bunyong Ketkhong, sinlapin haeng chat : ranat khaimuk lon bon chan yok - Sathian Duangchanthip (Krung Thep : Borisat Matichon : Chatchamnai doi Borisat Ngandi, 1992)
Life of Bunyong Ketkhong, b. 1920, a Thai classical musician; includes selected songs.
In Thai.
"Sinlapawatthanatham chabap phiset."
Keywords: Bunyong Ketkhong, -- 1920-; Composers -- Thailand -- Biography